Financial Feasibility Analysis of Perum Damri Serang Branch Business Study on the National Strategic Tourism Area Transportation Routes Tanjung Lesung and Sawarna - Gugun Gunawan; Arif Nugroho; Rizal Bahtiar; Nina Kurnia; Aditya Bayu Azi (Sean Institute, 2024)
This study aims to conduct a financial feasibility study of Perum DAMRI's business in the Serang branch with a focus on the transportation routes of Tanjung Lesung and Sawarna national tourism strategic areas. The study combines cost analysis, economic benefits, and financial aspects to evaluate DAMRI's operational performance on these routes. Through cost analysis, it was found that several factors such as vehicle operating costs, fuel, terminal levies, and tire replacement costs have an impact on DAMRI's profit margin. Furthermore, the economic benefit analysis shows that DAMRI can make a positive contribution to the national tourism area by providing better transportation access, but the results still need to be improved.However, when looking at the financial aspects, the two-year Net Present Value (NPV) analysis shows that DAMRI incurred losses in this project. A negative NPV, especially with a discount rate of 12.5%, indicates that the project did not achieve financial viability within the first two years of operation. However, the Internal Rate of Return (IRR) analysis reveals that the project has the potential to generate profitable returns, with an internal rate of return of approximately 13.68%. This suggests that if DAMRI can maintain or improve its operational efficiency, the project has the opportunity to be financially successful in the future. In conclusion, from various analysis perspectives, including BCR, NPV, and IRR, this DAMRI route business is currently not achieving the expected financial viability. Therefore, effective strategies and efforts are needed to ensure the viability and sustainability of DAMRI's operations on this route. Strategic measures could include improving operational efficiency, monitoring and controlling costs, and improving service management. More specific suggestions could involve improvements in cost management, fleet renewal, increased tourism promotion, cooperation with related parties, and the development of services that better suit passenger needs. With concerted efforts, DAMRI can maximize its business potential in Tanjung Lesung and Sawarna tourism areas and achieve better financial viability.